Choosing the Right Platform: A Comparative Analysis of E-Commerce Platforms and Their Impact on SME Performance - Halat, Oleh (Актуальні питання економічних наук, 2025)
The purpose of the article is to formulate and substantiate a comparative approach to selecting an e-commerce platform for small and medium-sized enterprises (SMEs), as well as to evaluate its impact on the performance of these companies. The relevance of the study is driven by the crucial role e-commerce platforms play in SME activities, as well as the fact that most enterprises select such platforms based primarily on cost and convenience criteria, ignoring their potential impact on overall company performance. Methods. The article employs a comparative analytical approach based on the technology-organization-environment (TOE) framework, the resource-based view (RBV), and multicriteria analysis methods. The empirical study covers five types of e-commerce platforms: hosted SaaS platforms, open-source content management systems with e-commerce plugins, customizable enterprise platforms, marketplace-oriented solutions, and low-code builders with e-commerce functionality. The analysis is conducted according to the criteria of implementation costs, administration complexity, scalability, integration with other information systems, marketing functionality, data analytics capabilities, security level, customer data ownership, and the potential impact of the platforms on SME performance. The results of scenario calculations conducted in the article allow for determining the suitability of each platform category for SMEs of various sizes. The research results demonstrate that there is no universally optimal type of e-commerce platform for all small and medium-sized enterprises. At the same time, it has been established that hosted SaaS platforms are the most suitable for description across various SME sizes, although their efficiency level and alignment with enterprise needs may vary depending on business operations and scale. Open-source platforms provide a high level of flexibility and data control but require an appropriate level of technical skills from SME employees. Customizable enterprise platforms are most effective for larger group SMEs with complex digital and information system requirements, whereas their use is less practical for micro-enterprises. Marketplace-oriented platforms are characterized by lower barriers to entry for SMEs, yet simultaneously limit enterprise autonomy and control over their digital presence. Low-cde website builders with built-in e-commerce functionality are suitable for establishing a baseline digital presence for SMEs but possess limited capabilities regarding scalability and data analytics. The conclusions note that the decision regarding which e-commerce platform to use has a significant impact on SME performance. The approach presented in this article makes it possible to identify the optimal platform for an SME of a specific size and with defined objectives